Prevalence of Malaria Plasmodium in Abeokuta, Nigeria - Okonko, I. O.; Soleye, F. A.; Amusan, T. A.; Ogun, A. A.; Udeze, A. O.; Nkang, A. O.; Ejembi, J.; Faleye, T. O. C. (Malaysian Journal of Microbiology, 2009)
This study reports the prevalence of malaria caused by plasmodium between genders in Abeokuta, the capital city of Ogun State located in the forest zone of southwestern Nigeria between January 2002 and December 2004. Blood film examination for malaria parasites in 708 patients; 366 males and 342 females. Microscopic examination of thick films techniques was employed for this study. Of the 708 (100%) patients examined, 577 (81.5%) were Plasmodium-positive. A high malaria parasite prevalence rate of 81.5% was noted in this study. Female subjects were more infected (42.4%) than males (41.9%) however, there was no significant difference in the sex of the subjects studied (p=0.05). A high malaria parasite prevalence rate of 86.9% was noted in samples collected in year 2003 than in other years studied. There was significant difference in the years under study (p=0.05). This study shows that a good percentage of people were infested by malaria Plasmodium. This could be attributed to lack of adequate accommodation and poor sanitary conditions in the area under study. Although several efforts have been made to effectively control the high incidence of malaria in Nigeria, these have been largely unsuccessful due to a number of reasons such as irrigated urban agriculture which can be the malaria vector’s breeding ground in the city, stagnant gutters and swamps in our environment where mosquitoes breed in millions, and lack of political will and commitment of the government in its disease management program, low awareness of the magnitude of malaria problem, poor health practices by individuals and communities and resistance to drugs. Therefore, future interventions in Nigeria should be directed toward controlling malaria in the context of a moderate transmission setting; thus, large-scale distribution of insecticide-treated nets or widespread use of indoor residual spraying may be less cost-effective than enhanced surveillance with effective case management or focused larval control.